2022
DOI: 10.3892/mmr.2022.12653
|View full text |Cite
|
Sign up to set email alerts
|

Propofol postconditioning alleviates diabetic myocardial ischemia‑reperfusion injury via the miR‑200c‑3p/AdipoR2/STAT3 signaling pathway

Abstract: Myocardial ischemia/reperfusion (Mi/ri) syndrome is one of the leading causes of mortality and disability. Propofol postconditioning is known to improve myocardial ischemia/reperfusion injury (Mi/ri). The present study aimed to explore the mechanism of propofol postconditioning in diabetic Mi/ri. diabetic Mi/ri rat models were established and the rats were treated via propofol postconditioning. Staining with 2,3,5-triphenyl-2H-tetrazolium chloride, H&e staining, Tunel staining and eliSa were applied to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…MDA is a remarkable factor produced by OS, while SOD is a key antioxidant enzyme. Previous studies have presented that Dex can ease OS reactions and stress responses and PPF can inhibit the production of OS-related factors[ 43 , 44 ]. Our results showed that the combination of Dex and PPF better inhibited OS were used alone.…”
Section: Discussionmentioning
confidence: 99%
“…MDA is a remarkable factor produced by OS, while SOD is a key antioxidant enzyme. Previous studies have presented that Dex can ease OS reactions and stress responses and PPF can inhibit the production of OS-related factors[ 43 , 44 ]. Our results showed that the combination of Dex and PPF better inhibited OS were used alone.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-421 directly targets toll-like receptor 4 (TLR4), which is the upstream of the JAK2/STAT3 signaling pathway in inflammation in I/R injury ( 28 ). MiR-200c-3p directly targets at adiponectin receptor 2 (AdipoR2), which activated the STAT3 signaling pathway to suppress apoptosis in I/R ( 29 ). Fourth, STAT3 is the indirect target of miRNA to reduce the phosphorylation of STAT3.…”
Section: Stat3-mirna Crosstalk In Myocardial Infarctionmentioning
confidence: 99%